1 Answer | Add Yours
You should remember that the equation that represents the elasticity of demand is:`E= (p/Q)*(dQ)/(dp)`
Supposing that the equation of demand is `Q = sqrt(2700 - 3p^2), ` you need to differentiate the demand function with respect to p such that:
`(dQ)/(dp) = ((2700 - 3p^2)')/(2sqrt(2700 - 3p^2))`
`(dQ)/(dp) = (-6p)/(2sqrt(2700 - 3p^2))`
`(dQ)/(dp) = (-3p)/(sqrt(2700 - 3p^2))`
Notice that `(sqrt(2700 - 3p^2))!=0` , hence `2700 - 3p^2!=0` .
You need to find what are the values of p that cancel denominator such that:
`2700 - 3p^2 = 0 =gt - 3p^2 = -2700`
`p^2 = 900 =gt p_(1,2) = +-sqrt(900)`
`p = +-30`
You need to keep only the positive value for the price p, such that p=30.
Hence, evaluating the equation of elastic demand yields `(dQ)/(dp) = (-3p)/(sqrt(2700 - 3p^2))` over the restrictive domain `(0,30)U(30,oo).`
We’ve answered 333,687 questions. We can answer yours, too.Ask a question